Optimization of FSW parameters of AA6061-6 wt.% SiC composite plates - B.N. Venkatesh; Hebbal Umamaheshwar; P.N. Siddappa; S. Kousik; T.K. Nagaraja (Manufacturing Review, 2022)
AA6061-SiC composites are the most preferred materials for applications in the automobile and aerospace sector due to their superior properties. The FSW process is one of the novel solid states joining processes that overcome almost all the difficulties of the fusion welding process because the process that operates well below the melting point of the metals to be joined, consumes less energy, environment-friendly, and versatile, no shielding gas or filler metal is used. The welding parameters such as tool rotational speed, axial force, and tool pin profile play a major role in deciding the joint strength and hardness of the weld zone. Taguchi method was employed in this study to scrutinize the impact of welding processing factors, including rotational, speed, axial load, and pin profile on ultimate tensile strength, microhardness of weld zone. The results reveal that the welded joints produced at 750 rpm of tool rotational speed, the axial load of 6 kN using a square pin tool profile that exhibits higher UTS. The Vickers's hardness of AA6061-6 wt.% SiC composites was found to be superior at tool rotational speed of 900 rpm, the axial force of 6kN using cylindrical tool pin. The ANOVA Findings based on Vickers's hardness are tool profile: 53.84%, tool rotational speed: 20.16%, and axial force: 21.32%.